Poly (ADP-ribose) polymerase inhibitors in solid tumours: Systematic review and meta-analysis. (May 2021) - Schettini, Francesco; Giudici, Fabiola; Bernocchi, Ottavia; Sirico, Marianna; Corona, Silvia P.; Giuliano, Mario; Locci, Mariavittoria; Paris, Ida; Scambia, Giovanni; De Placido, Sabino; Rescigno, Pasquale; Prat, Aleix; et al.
Abstract: Background: Poly (ADP-ribose) polymerase-inhibitors (PARPis) showed antitumour activity in BRCA 1/2-mutated cancers, with more heterogeneous outcomes in tumours harbouring mutations that impair other genes involved in the DNA homologous recombination repair (HRR) or wild-type (wt). Methods: We conducted a systematic review and meta-analysis to better assess the role of PARPis in the treatment of metastatic solid tumours, with and without BRCA 1/2 mutations. The primary end-point was progression-free survival (PFS). The secondary end-points were overall response rate (ORR) and overall survival (OS). A random-effects model was applied. Results: Twenty-nine studies (8, 839 patients) were included. PFS was significantly improved (hazard ratio [HR]: 0.59, 95% confidence interval [CI]: 0.51–0.68, p < 0.001), without being affected by BRCA mutational status (p = 0.65). Significant subgroup differences were observed with regard to the tumour site (p = 0.001), line of therapy (p = 0.002), control arm (p < 0.001), type of PARPi (p < 0.001) and trials' phase (p = 0.006). PARPis were associated with ORR (relative risk: 1.35, 95% CI: 1.16–1.56, p < 0.001), with significant subgroup differences observed with regard to treatment line (p = 0.03), control arm (p = 0.04) and PARPis (p < 0.001) and independent of mutational status (p = 0.44), tumour site (p = 0.86) and trials' phase (p = 0.09). OS was significantly improved by PARPis (HR: 0.86, 95% CI: 0.80–0.92, p < 0.001), regardless of mutational status (p = 0.57), tumour site (p = 0.82), treatment line (p = 0.22), control arm (p = 0.21), PARPis (p = 0.30) and trials' phase (p = 0.26). Finally, an exploratory subgroup analysis showed a significant PFS improvement (HR: 0.51, 95% CI: 0.43–0.60, p < 0.001) with PARPis in BRCA -wt/HRR-deficient tumours. Conclusion: Our results confirm the efficacy of already approved PARPi-based treatments in BRCA 1/2-mutant solid tumours, support their role also in BRCA -independent HRR-deficient tumours and suggest a potentially broader efficacy in some wt tumours, perhaps with appropriate therapeutic partners. Prospective studies are warranted. Highlights: Twenty-nine trials with BRCA -mutant (mut) or wild-type (wt) cancers were included. Progression-free survival (PFS) was improved by PARP-inhibitors (is), independent of BRCA . Response rates were higher with PARPis, irrespective of BRCA status. Overall survival was improved by PARPis, independent of BRCA mutational status. PFS was improved by PARPis in cancers with homologous recombination deficiency.